Sonographic evaluation of diaphragmatic thickness and excursion as a predictor for successful extubation in mechanically ventilated preterm infants - Bahgat, Eslam (Eur J Pediatr, 2020)
Sonographic assessment of diaphragmatic thickness and excursion has been found to be an accurate tool in predicting successful extubation of adult patients from invasive mechanical ventilation. We aimed to evaluate the accuracy of sonographic assessment of diaphragmatic thickness and excursion in predicting successful extubation of preterm infants from invasive conventional mechanical ventilation. Preterm infants less than 32 weeks gestation who required invasive conventional mechanical ventilation were evaluated by diaphragmatic sonography within 1 h of their planned extubation. Infants were classified into successful or failed extubation groups based on their ability to stay off invasive mechanical ventilation for 72 h after extubation. Inspiratory and expiratory thickness plus excursion of the right and left hemidiaphragm as well as diaphragmatic thickening fraction (DTF) measures were compared between groups. We included 43 eligible infants, of whom 34 infants succeeded and 9 infants failed extubation. Infants in the successful extubation group had a significantly higher expiratory thickness of the right and left hemidiaphragm, excursion of the right and left hemidiaphragm, inspiratory thickness of the left hemidiaphragm, and DTF of the left hemidiaphragm compared with infants who failed extubation. The receiver-operating characteristic curves showed that excursion of the right and left hemidiaphragm has the highest significant accuracy in predicting successful extubation of preterm infants among all diaphragmatic parameters (AUC is 0.98 and 0.96, respectively; p value < 0.001 for both). Conclusion: We conclude that diaphragmatic excursion is a useful indicator for successful extubation of preterm infants from mechanical ventilation.